Teaching and learning English academic writing in Malaysian tertiary context - Azmar, Khairunnisa; Razali, Abu Bakar (Horizon Research Publishing, 2024)
English academic writing holds an integral part in higher education. It entails a formal style of writing where writers are compelled to follow academic writing conventions to support their claims and arguments in writing. Despite the importance of English academic writing, majority of lecturers and students especially those in the context of English as second or foreign language (ESL/EFL) view English academic writing as challenging to teach and learn. This is because writers are obliged to utilize their cognitive, writing, and academic literacy skills while also having to use English language that might not be well familiar to them. This article reports on the issues faced by ESL lecturers in teaching English academic writing and issues in learning English academic writing among students in the Malaysian tertiary context. The authors also highlighted a few gaps identified from previous studies and suggested a few suggestions for teaching and learning English academic writing and recommendations for future research to help close the gaps. This review would benefit related stakeholders especially ESL lecturers and students at the tertiary level, higher education institutions and curriculum and policy makers.